The Effect of Providing First Aid Education on Accidents (P3K) in Increasing The Knowledge and Motivation of Members of The Youth Red Cross (PMR) at Muhammadiyah 1 High School In Jambi City - Andi Subandi; Dwi Noerjoedianto; Iis Hartini; Muhammad Taqwa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Accidents or injuries can happen anywhere, anytime, even in the school environment. Wherever an accident occurs, it is necessary to get immediate help to reduce the danger and immediately go to the nearest health facility. The low level of knowledge and motivation of PMR members will be a big problem, because PMR members are trained as first aiders in schools before the victim is sent to the next health facility. This study used a quantitative pre-experimental type with a one group pretest-posttest design approach. The population in this study were all members of PMR SMA Muhammadiyah 1 Jambi City. The sample in this study was 35 students using the total sampling technique. The independent variable of this study is first aid education and the dependent is the knowledge and motivation of PMR members. The research instrument used a 2-time questionnaire using the Wilcoxon statistical test. The results showed that before the intervention, some respondents had sufficient knowledge as many as 27 respondents (77.1%) and after the intervention the respondents had good knowledge as many as 35 respondents (100%). Motivation of PMR members before being given the intervention, most respondents were moderately motivated with a total of 31 respondents (88.6%) and motivation after being given the intervention all respondents were highly motivated as many as 35 respondents (100%). Wilcoxon statistical test results there is an effect of first aid education on knowledge with a significance value of 0.001 (p Subscribe to DeepL Pro to edit this document. Visit www.DeepL.com/pro for more information. < 0.05) and motivation with a significance value of 0.001 (p < 0.05). This study shows that first aid education has an influence on increasing the knowledge and motivation of PMR members at Muhammadiyah 1 High School in Jambi City. PMR members are expected to be able to increase motivation and relevant knowledge about first aid in accidents, as well as motivation towards others and themselves.